Emerging trends in electrical, electronic and communications engineering : proceedings of the first International Conference on Electrical, Electronic and Communications Engineering (ELECOM 2016), Bagatelle, Mauritius, November 25 -27, 2016 /: proceedings of the first International Conference on Electrical, Electronic and Communications Engineering (ELECOM 2016), Bagatelle, Mauritius, November 25 -27, 2016. (2017) - Unknown
No abstract available